2016
DOI: 10.1002/1873-3468.12368
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of docosahexaenoic acid (DHA; 22:6n‐3) in human cells: direct retroconversion of DHA to eicosapentaenoic acid (20:5n‐3) dominates over elongation to tetracosahexaenoic acid (24:6n‐3)

Abstract: Docosahexaenoic acid (22:6n-3) supplementation in humans causes eicosapentaenoic acid (20:5n-3) levels to rise in plasma, but not in neural tissue where 22:6n-3 is the major omega-3 in phospholipids. We determined whether neuronal cells (Y79 and SK-N-SH) metabolize 22:6n-3 differently from non-neuronal cells (MCF7 and HepG2). We observed that 13C-labeled 22:6n-3 was primarily esterified into cell lipids. We also observed that retroconversion of 22:6n-3 to 20:5n-3 was 5- to 6-fold greater in non-neural compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…The preferential metabolic route for DHA must be β-oxidation, although other metabolic transformations cannot be ruled out. In fact, DHA can be converted into EPA (eicosapentaenoic acid, C20:5 n-3) (Park et al, 2016) and indeed, we detected a significant increase in EPA after DHA stimulation (see Table 2). Likewise, there was a similar upregulation of docosapentaenoic acid (DPA, C22:5 n-3) following DHA stimulation (see Table 2), suggesting that DHA could be converted into DPA.…”
Section: Dha-h and Dha Are Incorporated And Accumulated Distinctly Insupporting
confidence: 53%
“…The preferential metabolic route for DHA must be β-oxidation, although other metabolic transformations cannot be ruled out. In fact, DHA can be converted into EPA (eicosapentaenoic acid, C20:5 n-3) (Park et al, 2016) and indeed, we detected a significant increase in EPA after DHA stimulation (see Table 2). Likewise, there was a similar upregulation of docosapentaenoic acid (DPA, C22:5 n-3) following DHA stimulation (see Table 2), suggesting that DHA could be converted into DPA.…”
Section: Dha-h and Dha Are Incorporated And Accumulated Distinctly Insupporting
confidence: 53%
“…It is possible that the n-3 PUFA biosynthetic pathway behaves very differently in isolated liver microsomes or hepatocytes compared with in living mammals. In such a scenario, DPAn-3 could be desaturated directly to DHA by a 4-desaturase as evidenced in human cells (4,5), further elongated to THA, and then quickly -oxidized back to DHA in the peroxisome. Interestingly, cells grown in the presence of labeled DHA demonstrated an up to 5-fold higher retroconversion of DHA to EPA compared with elongation to THA (4).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although synthesis secretion of DHA from THA is significantly higher than THA from DHA, additional studies feeding DHA would be expected to yield more similar rates between the directions. In addition, the recent application of these infusion models to humans (24), the evidence from human cell lines suggesting the bypassing of the Sprecher pathway (4,5), and the potentially very low 2 H 5 -THA tracer requirements make the implementation of human THA infusions an exciting future step. In particular, the comparison of DHA synthesis rates between individuals with peroxisomal disorders, such as Zellweger's syndrome, would lead to an even more comprehensive understanding of such conditions.…”
mentioning
confidence: 99%
“…Retro‐conversion of DHA to EPA occurs in the peroxisomes via β‐oxidation to remove the double bond at position 4. Retro‐conversion of DHA is more common in non‐neural cells than neural cells (Park et al, 2016). However, recently it was shown that increased plasma level of EPA in human following DHA supplementation did not occur via retro‐conversion rather a result of slowed metabolism and/or accumulation of plasma EPA (Metherel et al, 2019).…”
Section: Dietary and Metabolic Sources Of Dha And Its Worldwide Consumentioning
confidence: 99%